2016
DOI: 10.9745/ghsp-d-16-00052
|View full text |Cite
|
Sign up to set email alerts
|

Postabortion Care: 20 Years of Strong Evidence on Emergency Treatment, Family Planning, and Other Programming Components

Abstract: Twenty years of postabortion care (PAC) studies yield strong evidence that:Misoprostol and vacuum aspiration are comparable in safety and effectiveness for treating incomplete abortion.Misoprostol, which can be provided by trained nurses and midwives, shows substantial promise for extending PAC services to secondary hospitals and primary health posts.Postabortion family planning uptake generally increases rapidly-and unintended pregnancies and repeat abortions can decline as a result-when a range of free contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
69
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(79 citation statements)
references
References 64 publications
5
69
0
5
Order By: Relevance
“…Rural PAC patients in Zimbabwe have significantly higher odds of developing higher severity post-abortion complications when compared to urban PAC patients [3]. Uterine evacuation is a safe procedure that can and should be performed at the primary level [9]. Therefore, it is important for public primary health centers to be equipped and providers trained to use appropriate uterine evacuation technologies, such as misoprostol, to avoid delays in treatment associated with referring patients to other facilities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rural PAC patients in Zimbabwe have significantly higher odds of developing higher severity post-abortion complications when compared to urban PAC patients [3]. Uterine evacuation is a safe procedure that can and should be performed at the primary level [9]. Therefore, it is important for public primary health centers to be equipped and providers trained to use appropriate uterine evacuation technologies, such as misoprostol, to avoid delays in treatment associated with referring patients to other facilities.…”
Section: Discussionmentioning
confidence: 99%
“…Since abortion is one of the main causes of maternal death, it is essential to understand the coverage and quality of abortion care in a context of high maternal mortality and restrictive abortion laws, like Zimbabwe. While there is a body of literature on measuring the quality of abortion care, there is inconsistency in how the quality of abortion care is measured [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Programs should ensure that both MVA and misoprostol are available at HFs, and women should be informed of appropriate treatment options, staff should be trained, and communities should be informed. 19 EmONC guidelines were available at fewer than half of public and private HFs. These guidelines indicate managing incomplete abortions and miscarriage using MVA as a signal function but lack the medical treatment of incomplete abortion and family planning component of PAC.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Evidence shows that postabortion family planning is a high-impact practice that results in higher family planning uptake when it is provided proactively at the same time and location where a woman receives facility-based PAC. 19,20 A 2010 study to assess availability of PAC in Afghanistan showed that although designated emergency obstetric facilities in Afghanistan generally have most supplies and equipment for PAC available, capacity of health care providers to deliver PAC is limited. Training on PAC-related skills was recommended in 2015 to all SBAs.…”
mentioning
confidence: 99%